2021
DOI: 10.1038/s41467-021-24292-5
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of selective nuclear import and export with a perfectly repeated 12mer GLFG peptide

Abstract: The permeability barrier of nuclear pore complexes (NPCs) controls nucleocytoplasmic transport. It retains inert macromolecules while allowing facilitated passage of importins and exportins, which in turn shuttle cargo into or out of cell nuclei. The barrier can be described as a condensed phase assembled from cohesive FG repeat domains. NPCs contain several distinct FG domains, each comprising variable repeats. Nevertheless, we now found that sequence heterogeneity is no fundamental requirement for barrier fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(61 citation statements)
references
References 94 publications
0
61
0
Order By: Relevance
“…Table 1 for a list of symbols): where R is the gas constant (8.31 J/mol·K) and T the absolute temperature in Kelvin. The G 0 term of the formula considers here that the fluorophore is (weakly) FG-philic 29 and compensates the bias from the labelling. The fit of the data revealed that one repeat unit contributes 255 J/mol to the partition equilibrium, when measured at 21°C (294 K) and 150 mM NaCl.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 for a list of symbols): where R is the gas constant (8.31 J/mol·K) and T the absolute temperature in Kelvin. The G 0 term of the formula considers here that the fluorophore is (weakly) FG-philic 29 and compensates the bias from the labelling. The fit of the data revealed that one repeat unit contributes 255 J/mol to the partition equilibrium, when measured at 21°C (294 K) and 150 mM NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…It was designed to match the conserved features of native Nup98 FG domains as closely as possible, including the high FG motif number/ density, compositional bias, and charge-depletion. The FG phase assembled from prf.GLFG 52x12 captures the biophysical properties and transport selectivity of the original Nup98 FG phase very well indeed 29,35 and even recapitulates RanGTPasecontrolled cargo import and export scenarios 29 . It thus represents the simplest possible experimental model of NPC-typical transport selectivity.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Conversely, the transport carrier proteins are able to penetrate the meshwork because the energy liberated from their binding to hydrophobic cores of the FG-nucleoporins is sufficient to overcome the breaking of cohesive contacts among the FG-nucleoporins [ 19 , 35 ] needed to facilitate their movement through the transport channel. Cohesive interactions among the FG-nucleoporins are thought to derive from a combination of hydrophobic, electrostatic, and other attractions, and appear to contribute to the generation of a dense meshwork within the central nuclear pore channel that impairs the movement of macromolecules [ 18 , 19 , 22 , 23 , 34 , 36 , 37 , 38 ].…”
Section: Nuclear Transport Machinerymentioning
confidence: 99%